Civil-military relations in Namibia, 1990-2005 - Mwange, Matomola Vincent (My University, 2009)
The period 1960-63 saw the independence of many African countries. Since then, the continent has experienced numerous military coups, attempted coups or military interference in politics. Consequently, many countries have found it important that the power of the military be used responsibly and for the benefit of the society. To achieve this they opted for subordination of the military to civilian authorities, yet coups and coup attempts have persisted. In contrast to this scenario on the continent there has not been a coup d’etat, attempted coup d’etat, or any form of unacceptable influence over the political process by the military in Namibia since independence in 1990. The purpose of this study was to determine the political institutions in the country that are necessary for democratic civil-military relations and how they have effectively contributed to the prevailing peace and stability in Namibia. Much has been written on civil-military relations; however, very little research has been produced on democratic civil-military relations in Namibia since independence. This thesis is a study of how Namibia took the path of democratic civil-military relations that have ensured civil control over the military. The research was informed by examining the generally held assumptions about civil-military relations as espoused in the literature to better understand the phenomenon of civil-military relations in Namibia that has ensured civil supremacy over the military. In this regard, the study was a qualitative method of research. This method helped to describe the concepts of civil-military relations using the guiding theoretical framework and thereafter helped to examine civil-military relations being applied in Namibia. One of the main findings of the research was that civil-military relations in Namibia are characterised by Western liberal civil-military relations traditions. The nature of civil-military relations in Namibia was influenced by factors such as historical legacy, the liberation struggle experience and the international context that shaped the Namibian state. It was also established through this study that the two main shortcomings of civil-military relations in the country were the inadequacy in parliamentary oversight of the defence and security, and serious deficiencies with regard to limited participation of civil society.
Keywords: Civil-military relations; Namibia